18F-FDG-PET Scanning Confirmed Infected Intracardiac Device-Leads with Abiotrophia defectiva - Sonja van Roeden; Hans Hartog; Vivian Bongers; Steven Thijsen; Sanjay Sankatsing (Case Reports in Cardiology)
Abiotrophia species are relatively slow growing pathogens, which may be present as commensal flora. However, invasive infections are frequently reported, like endocarditis, septic arthritis, osteomyelitis, and many other types of infection. In this case report we describe a 65-year-old male patient with an intracardiac device- (ICD-) lead infection caused by Abiotrophia defectiva. Diagnosis was confirmed by 18F-FDG-PET scanning. This is remarkable, since Abiotrophia defectiva is a slow growing pathogen causing low-grade infections. This case demonstrates that although infection of ICD-leads cannot be excluded in case of 18F-FDG-PET-negative findings, positive findings are highly suggestive for infection.